Understanding the mechanism of ulcerative colitis-induced colorectal cancer and revealing the potential of Dillenia Indica in its management - Sujata Paul; El Bethel Lalthavel Hmar; Hemanta Kumar Sharma (Elsevier, 2024)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) that significantly increases the risk of developing colorectal cancer (CRC). The overall prevalence of UC-induced CRC is on the rise due to the rapidly increasing frequency of UC. It is widely acknowledged that chronic inflammation that persists for a long period is a significant contributing factor to the development of CRC in individuals with UC. The activation of various proinflammatory pathways, such as nuclear factor kappa B (NF-κB), interleukin-6/signal transducer and activator of transcription 3 (IL-6/STAT3), cyclooxygenase-2/prostaglandin E2 (COX-2/PGE2), and interleukin-23/T-helper 17 (IL-23/Th17), and gut microbiota contributes to the initiation and progression of tumorigenesis by a different mechanism, such as triggering the production of inflammatory mediators, increasing the expression of antiapoptotic genes, and stimulating cell proliferation as well as angiogenesis. Managing this risk and finding potential nutraceutical interventions, such as Dillenia indica (DI), is of significant interest. This review delves into the literature concerning the mechanism correlated to the development of CRC in UC individuals and investigates the potential of DI, as a nutraceutical in managing this rapid risk of UC-CRC. By examining the different mechanisms involved in UC-induced CRC, we aim to provide insight into the therapeutic promise of DI in mitigating these mechanisms.